WINTER WHEAT MIXTURES INFLUENCE GRAIN RHEOLOGICAL AND MIXOLAB QUALITY - Trong Nghia HOANG; Marek KOPECKÝ; Petr KONVALINA (Journal of Applied Life Sciences and Environment)
This study aims to investigate the effect of a mixture of winter wheat varieties on grain rheological characteristics and the quality of wheat flour analyzed by Mixolab. In the 2019-2020 growing season, a small plots experiment was carried out in an organically certified field in the Czech Republic. The experiment was conducted by randomized complete block design with three replicates, four winter wheat (Triticum aestivum L.) varieties with four mixtures of the same varieties in equal proportions. Based on the results, the expected grain yield was not achieved. The quality of wheat productivity was significantly different among treatments in terms of protein content, wet gluten, sedimentation value, and falling number (P < 0.001). Protein content ranged between 8.04% and 9.85%, mixtures of Butterfly + Lorien and Illusion + Lorien were higher in protein than Illusion and Vanessa varieties and their combination. The highest wet gluten was found under mixtures of Butterfly + Lorien varieties (19.34%) while sowing Butterfly variety gave the highest Zeleny test and falling number compared to other treatments. Butterfly + Lorien and Butterfly + Vanessa mixtures obtained good results for falling number at 250.67 and 272.67 seconds. There were significant differences in rheological quality parameters of winter wheat varieties analyzed by Mixolab including stability, weakening of protein, and starch (P < 0.01 and P < 0.001, except slope gamma). Although the observed benefits were limited to grain yield, mixtures of individual cultivars appear to be a potential tool to improve overall crop performance (grain quality).